Damselflies of the genus Argia Rambur, 1842 (Odonata: Coenagrionidae) from Mexico, Central America and the Lesser Antilles with descriptions of five new species - Garrison, Rosser W.; Ellenrieder, Natalia Von (Zootaxa, 2022)
A total of 73 species of Argia Rambur, 1842 are reported as present from Mexico, Central America and the Lesser Antilles, of which five are new to science and are described here: Argia annae n. sp. (holotype ♂: MEXICO, Veracruz, Puente Texolo, roadside seepages near bridge, 19.4028°N, 96.9867°W, 1065 m, 17 June 2009, Rosser W. Garrison & Natalia von Ellenrieder leg., in CSCA), Argia gonzalezi n. sp. (holotype ♂: MEXICO, Chiapas, 3.5 mi east of Rayón, stream, approximately 17.2058°N, 92.9700°W, 1676 m, 16 July 1965, Dennis R. Paulson leg., in CNIN), A. noveloi n. sp. (holotype ♂: MEXICO, Veracruz, Puente Texolo, 19.4028°N, 96.9867°W, 1065 m, 26 August 1988, Rosser W. Garrison leg., in INECOL), A. paludicola n. sp. (holotype ♂: U. S. A., Arizona, Apache County, Bog Tank, north of Highway 260, 34.0467°N, 109.683°W, 1400 m, 1 July 2016, Pierre Deviche leg., in CSCA) and A. paulsoni n. sp. (holotype ♂: COSTA RICA, San José, 7.5 km northeast of Londres, on road to Rancho Tinamú Lodge, 9.4856°N, 83.9911°W, 700 m, 5 July 2019, William A. Haber leg., in UNH). Redescriptions of male and female are provided for the following species: Argia calida (Hagen, 1861), A. chelata Calvert, 1902, A. deami Calvert, 1902, A. fulgida Navás, 1934, A. herberti Calvert, 1902, A. johannella Calvert, 1907, A. mayi González-Soriano, 2012, A. percellulata Calvert, 1902, A. pocomana Calvert, 1907, A. rogersi Calvert, 1902, A. talamanca Calvert, 1907, A. terira Calvert, 1907, A. underwoodi Calvert, 1907, and A. variabilis Selys, 1865. All 73 species are measured, illustrated, and distinguished from their congeners. The following synonymies are suggested based on examination of type material: A. wilsoni Calvert, 1902, a junior synonym of A. calida (Hagen, 1861), A. plana Calvert, 1902, a junior synonym of A. funebris (Hagen, 1861), and A. trifoliata Fraser, 1942 (Fig. 736), a junior synonym of A. variegata Förster, 1914. Lectotypes are designated for Agrion calidum Hagen, 1861, Agrion funebris Hagen, 1861, and Argia variabilis Selys, 1865. Keys to the 73 known Argia species from Mexico, Middle America and the Lesser Antilles are provided as well as distribution maps based on an examination of over 16,000 specimens.